The Pathogenesis of Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome: A Review of Current Research - Barbara Kraszewska-Głomba; Agnieszka Matkowska-Kocjan; Leszek Szenborn (Hindawi Limited, 2015)
Background. PFAPA syndrome is a chronic disease that is characterized by recurrent episodes of high fever, aphthous stomatitis, pharyngitis, and cervical adenitis. Knowledge regarding the etiology of PFAPA is limited. Objectives. To provide up-to-date information considering etiology of PFAPA syndrome, by summarizing what has been explored and established in this area so far. Materials and Methods. PubMed, Web of Science, and Scopus databases were searched for pertinent reports. Eventually 19 articles were selected. The results were classified into categories regarding three areas of interest: familial occurrence, genetic basis, and immunological mechanisms of PFAPA. Results. Recent findings suggest that there is a familial tendency to PFAPA but the level of evidence does not warrant definite conclusions. The absence of a clear monogenic trait indicates a heterogenous, polygenic, or complex inheritance of PFAPA syndrome. As two mutations with a possible functional effect on the inflammasomes (MEFV E148Q and NLRP3 Q703K) have been found in several PFAPA cohorts, the role of inflammasome-related genes in PFAPA pathogenesis cannot be excluded. Immunological mechanisms of PFAPA involve an abnormal, IL-1β dependent innate immune response to an environmental trigger, which leads to Th1-driven inflammation expressed by recruitment of T-cells to the periphery.